2023
DOI: 10.1371/journal.pone.0283239
|View full text |Cite
|
Sign up to set email alerts
|

Burnout among healthcare providers: Its prevalence and association with anxiety and depression during the COVID-19 pandemic in Macao, China

Abstract: Introduction Burnout in healthcare providers (HPs) might lead to negative consequences at personal, patient-care and healthcare system levels especially during the COVID-19 pandemic. This study aimed to investigate the prevalence of burnout and the contributing variables, and to explore how, from health workforce management perspective, HPs’ experiences related to carrying out COVID-19 duties would be associated with their burnout. Methods A cross-sectional, open online survey, informed by physical and psych… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 86 publications
2
6
0
Order By: Relevance
“…Lastly, burnout is a factor that is significantly associated with depression. This is supported by the studies conducted in Southeastern Anatolia from Diyarbakir, Turkey [ 4 ] and in Macao, China [ 41 ]. This might be due to a person who has burnout feeling as though “it’s never enough” and then might start to feel hopeless or lack all emotion in his or her job and be prone to depression.…”
Section: Discussionsupporting
confidence: 59%
“…Lastly, burnout is a factor that is significantly associated with depression. This is supported by the studies conducted in Southeastern Anatolia from Diyarbakir, Turkey [ 4 ] and in Macao, China [ 41 ]. This might be due to a person who has burnout feeling as though “it’s never enough” and then might start to feel hopeless or lack all emotion in his or her job and be prone to depression.…”
Section: Discussionsupporting
confidence: 59%
“…The timing of the collection of questionnaire responses when the COVID-19 pandemic was under control in Germany might have influenced the results of the present study. However, against the background of persistently high burnout rates in times of low COVID-19 incidence rates [ 28 ], this seems to be a negligible factor.…”
Section: Discussionmentioning
confidence: 99%
“…The identification of nurses at risk and functional coping strategies can enhance nurses’ professional quality of life [ 27 ], which requires readiness for intervention by policy makers, hospital facilities, and individuals [ 28 ]. However, individualized coping strategies tailored to the specific needs of nurses are difficult to implement, as few studies have elucidated the physical and emotional stress characteristics of nurses in functional areas other than critical care and emergency nursing.…”
Section: Introductionmentioning
confidence: 99%
“…The Link Burnout Questionnaire (LBQ) [16,17] and the Socio-Demographic Questionnaire (SDQ) were used in the presented project. The LBQ is designed to measure occupational burnout in people working in professions related to helping other people and teaching using four subscales (six items each): (1) psychophysical exhaustion (the dimension concerning the assessment of one's own psychophysical resources, questions 1, 7, 10, 16, 22, 24); (2) deterioration of relationships with users (dimension describing the quality of relationships with patients, questions 3, 5, 12, 14, 18, 23); (3) job ineffectiveness (dimension referring to the assessment of one's own professional competences, questions 2,8,11,13,17,20); and (4) disappointment (dimension of existential expectations, questions 4,6,9,15,19,21). The method of providing answers is based on a 6-point Likert scale, the individual points of which correspond to the following categories: never-1 point; rarely-2 points; once or more times a month-3 points; more or less every week-4 points; several times a week-5 points; and every day-6 points.…”
Section: Variables and Measurementsmentioning
confidence: 99%
“…Nurse burnout was an important public health issue even before the outbreak of the pandemic. Moreover, studies have observed that ongoing viral epidemics, including COVID-19, have a negative impact and exacerbate the problem [11][12][13][14][15]. Professional burnout is a response to chronic fatigue and stressors at work.…”
Section: Introductionmentioning
confidence: 99%